2013
DOI: 10.2147/ppa.s39887
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between psoriasis symptom severity and quality of life, work productivity, and activity impairment among patients with moderate-to-severe psoriasis using structural equation modeling

Abstract: BackgroundPlaque psoriasis is a chronic disease characterized by scaly plaques on the skin that can itch and bleed. Psoriasis covering over 10% of the body is classified as moderate to severe, and can impact patient quality of life.ObjectivesTo assess the relationship between plaque psoriasis self-reported severity symptoms and health-related quality of life, work productivity, and activity impairment among patients with moderate-to-severe psoriasis.MethodsThe study sample included 199 patients recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…[ 25 ] Several studies have investigated the relationship between physical activity and psoriasis, and some of these studies have found contradictory data. [ 26 30 ] Some scholars believe that physical activity is likely to aggravate the severity of psoriasis, while others believe that psoriasis is likely to improve following a course of voluntary exercise. In our clinic, a large number of patients with psoriatic skin symptoms and mental health problems (anxiety, tension, low self-esteem, isolation, and depression) showed improvements in their condition following varying degrees of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Several studies have investigated the relationship between physical activity and psoriasis, and some of these studies have found contradictory data. [ 26 30 ] Some scholars believe that physical activity is likely to aggravate the severity of psoriasis, while others believe that psoriasis is likely to improve following a course of voluntary exercise. In our clinic, a large number of patients with psoriatic skin symptoms and mental health problems (anxiety, tension, low self-esteem, isolation, and depression) showed improvements in their condition following varying degrees of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Pain has been self-reported as a symptom in 17–83% of patients with plaque psoriasis ( 1–4 ). Skin redness is also a common symptom in patients with plaque psoriasis and has been self-reported in 71–79% of patients ( 3 , 5 ). Patients with psoriasis who experience pain are more likely than patients without pain to miss work (odds ratio [OR] = 1.78; 95% confidence interval [CI] = 1.30–4.10), experience reduced productivity while at work (OR = 1.53; 95% CI = 1.12–2.09) and have difficulty performing daily activities (OR = 1.53; 95% CI = 1.19–1.96) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Skin redness is also a common symptom in patients with plaque psoriasis and has been self-reported in 71–79% of patients ( 3 , 5 ). Patients with psoriasis who experience pain are more likely than patients without pain to miss work (odds ratio [OR] = 1.78; 95% confidence interval [CI] = 1.30–4.10), experience reduced productivity while at work (OR = 1.53; 95% CI = 1.12–2.09) and have difficulty performing daily activities (OR = 1.53; 95% CI = 1.19–1.96) ( 3 ). Notably, pain associated with psoriasis has a severe negative effect on sleep, which profoundly affects health-related quality of life (HRQoL) ( 1 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is particularly pertinent given recent reports from a population‐based survey, in which 43% of more than 3000 patients with psoriasis indicated that pruritus was the most bothersome symptom 10, 34. In addition, pruritus is more likely to result in the absence from work than pain or scaling, and leads to reduced productivity 35. Therefore, for patients with psoriasis who are distressed by pruritus, tofacitinib may potentially represent an important future treatment option.…”
Section: Discussionmentioning
confidence: 95%